2022
DOI: 10.3389/fneur.2022.796882
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Health System Case Series of New-Onset CNS Inflammatory Disorders Temporally Associated With mRNA-Based SARS-CoV-2 Vaccines

Abstract: BackgroundSince 2020, over 250 million doses of mRNA-based SARS-CoV-2 vaccines have been administered in the United States and hundreds of millions worldwide between the Pfizer-BioNTech and Moderna SARS-CoV-2 vaccines. To date, there have been rare reports associating mRNA-based SARS-CoV-2 vaccines with episodes of inflammatory and autoimmune CNS disorders. We report a case series of five patients with new-onset neurological disorders of inflammatory or immunological origin temporally associated with these vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 51 publications
(76 reference statements)
0
15
0
Order By: Relevance
“…Next, 88 studies were excluded via title and abstract evaluation. Finally, after the full-text screening, 20 studies with a total of 54 cases were entered into our systematic review [ [6] , [18] , [20] , [21] , [22] , [23] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Next, 88 studies were excluded via title and abstract evaluation. Finally, after the full-text screening, 20 studies with a total of 54 cases were entered into our systematic review [ [6] , [18] , [20] , [21] , [22] , [23] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…A study reviewing case reports and case series reported the occurrence of variable central and peripheral nervous system complications in patients receiving gene-based vaccines including transverse myelitis, Guillain-Barré syndrome, and cerebral venous sinus thrombosis (Sriwastava et al, 2022). It was noticed that post-mRNA-based SARS-CoV-2 vaccines, either the first or the second dose, were complicated by new-onset neuroimmunological disorders like acute disseminated encephalomyelitis, neuromyelitis optica spectrum disorder, and multiple sclerosis (Ballout et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Another 11 records were identified from citation ( n = 1) or Google Scholar searches ( n = 10) and were also included. Finally, 31 articles met the eligibility criteria 15,24–53 and were included in the present systematic review (Figure 1).…”
Section: Resultsmentioning
confidence: 99%